PENGETAHUAN DAN SIKAP PERAWAT TENTANG MOBILISASI DINI PASIEN DI ICU RSUD PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - Nofiyanto, Muhamat; Munif, Muhamad; Darussalam, Miftafu (MEDIA ILMU KESEHATAN, 2017)
Background: Early mobilization is necessary in critically ill patients in Intensive Care Unit (ICU) to prevent hypovolemia which endangers patient’s life. The role of nurses in early mobilization is important by providing explanations and motivating patients to achieve the purpose of healing. Guidance and intensive intervention from nurses can reduce the recurrence of disease. Objective: To investigate the level of knowledge and attitude of nurses on patients early mobilization in ICU of RSUD Panembahan Senopati Bantul. Method: A descriptive, cross sectional study, was applied on 20 nurses in ICU of RSUD Panembahan Senopati Bantul. Univariate data analysis was administered to characteristics of respondents, knowledge, attitudes, and cross-tabulations. Result: Most of nurses have good level of knowledge (70%), and on attitude domain, most nurses are being supportive (75%) in terms of early mobilization to patients. Nurses whose age are 22-35 years old (10%), male (10%), have been working for 1 month up to 5 years (10%), have background of 3 years diploma in nursing (10%) fall into poor knowledge category. Similar characteristics contribute to attitude domain where nurses whose age are 22-35 years old (25%), male (15%), have been working for 1 month up to 5 years (25%), have background of 3 years diploma in nursing (35%) are placed into unsupportive category. Conclusion: The level of knowledge of nurses on patients early mobilization is in good category where the attitude is in supportive category. Keywords: Knowledge, attitude of nurses, early mobilization.